Software business : 8th International Conference, ICSOB 2017, Essen, Germany, June 12-13, 2017, Proceedings /: 8th International Conference, ICSOB 2017, Essen, Germany, June 12-13, 2017, Proceedings. (2017) - Unknown
No abstract available